ANÁLISIS DE LA SENTENCIA N°. 113-14-SEP-CC, EMITIDA POR LA CORTE CONSTITUCIONAL DEL ECUADOR, EN EL CASO LA COCHA - Chimborazo Palma, Mayra Jeaneth (2015)
Active entitled under the Act states that resolution by the indigenous authorities of the Community of La Cocha, Sunday May 9, 2010 at 19:00 or so, in the center of the parish Zumbahua, indigenous population Kichwa speaker Pujilí province of Cotopaxi, there was the murder of his brother Marco Antonio Olivo Pallo. Based on items 1 7 1 of the Constitution of the Republic and 343 of the Code of Judicial Function, the indigenous authorities of the communities of La Cocha and Guantopolo they heard the case. Sunday 1st May 6, 2010 and Sunday, May 23, 2010 established the guilt of the five indigenous youth in the community of Guantopolo and imposed sanctions under indigenous justice. The Constitutional Court has ratified the decisions made around the trial of the five involved in the murder of Marco Antonio Olivo Palio, however, after four years of waiting for the resolution, they have not resolved the core of, respect, that criminal offenses if any, would be appropriate application of indigenous justice. For it is clear that the Constitution of the Republic of Ecuador (Art. 171), Convention 169 (Art. 8 paragraph 2), the Organic Code of the Judiciary (art. 343), Organic Law of Guarantees Constitutional courts and Control (Art. 65), would be a dead letter, because so far has not been prepared, guidelines regarding the skills of indigenous justice or that would reach.